High incidence of oncogenic HPV genotypes found in women from Southern Brazil - Entiauspe, Ludmila G (Sociedade Brasileira de Microbiologia, 2014)
Oncogenic HPV genotypes are strongly associated with premalignant and malignant cervical lesion. The purpose was to determine human papillomavirus (HPV) prevalence and genotypes, and to estimate cervical cancer risk factor associations. Cervical samples were obtained from 251 women seeking gynecological care at the Pelotas School of Medicine Clinic. This is a cross-sectional study. HPV-DNA was amplified by nested-PCR using MY09/11 and GP5/6 primers, and the sequencing was used for genotyping. Sociodemographic and behavioral risk factors were obtained by closed questionnaire, and its relationship to HPV infection prevalence were analyzed. Statistical analyses were performed using SPSS 16.0 software, and differences were considered significant at p < 0.05. As results, the prevalence of HPV infection was 29.9%. The most frequent genotype was HPV-16 (41.3%), followed by HPV-18 (17.3%), and HPV-33 (9.3%). Others nine HPV genotypes were also found. On this population, prevalence of oncogenic HPV genotypes was high, but does not seem to confer relationship with the risk factors investigated. Future investigations in larger populations are necessary, for the proposition of more appropriated monitoring strategies and treatment according to the Brazilian health service reality, as well as patients.